Pengaruh Dimensi Brand Equity (Ekuitas Merek) terhadap Keputusan Pembelian Kartu Telepon Selular Telkomsel di Kota Malang - Nur Ida Iriani (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Nowadays, the business competition of handset operator cellular in Indonesia are more competitive. This condition makes Telkomsel is not only depend on product differentiation and price leader, which is easy to follow. Brand that have a several attribute equity will create a positive brand image in the consumer mind. The purpose of the research is to analyze the influence of brand equity consisting of brand awareness, perceived quality, brand association and brand loyalty toward buying decision celular card of Telkomsel at Malang. The research method used quantitative approach in which variables are measured with Likert Scale. The sample amount is 100 respondent by incendental method. The primary data collection is by distributing quetionnaries. Data processing was used a application SPSS vs.15,0 for Windows (includes: validity and reliability analysis, classic assumption analysis, and hypotesis tested by multiple regression analysis). The result show that: (1) by collectively, the equity brand attribute having significant toward buying decision of consument. (2) by partially, there are significant influence of the all equity brand attributes consisting of perceived quality, brand association, and brand loyalty toward buying decision of consument. Then (3) brand loyalty having a dominant influence on buying decision.Keywords: brand equity, buying decision